Pelaksanaan Jaminan Kesehatan Nasional (JKN) Dalam Hal Mutu Layanan Kesehatan di Rumah Sakit Petala Bumi: Pelaksanaan Jaminan Kesehatan Nasional (JKN) Dalam Hal Mutu Layanan Kesehatan di Rumah Sakit Petala Bumi - Budi Hartono; Mitra Mitra; Nur Maimun (Jurnal Kesehatan Komunitas, 2019)
One of the policies implemented by the Government of Indonesia is the implementation of the National Health Insurance (JKN) program run by the Social Insurance Administration Organization (BPJS). However, over time the program was deemed detrimental to the community in terms of complicated procedures, inappropriate doctor services and limited drugs, and many more procedures that were deemed not to fit the needs of the community. The purpose of this research The purpose of this study was to find out the implementation of JKN in terms of quality of health services at Pekanbaru Petala Bumi Hospital. This is a research method qualitative purposive sampling, to technique two informants hospitals and 2. the patients data collection is done with the observation/ observation in-depth interviews, and group interviews. The research technical competence officials always update sip, doctor affordability and accessibility hospital, accessible the health services management, instuksi follow in curbing bpjs, policy. in supporting the availability of tools, BPJS does not provide tools but hospitals that provide, but hospitals have standards that are in accordance with regulations, patient health services have clinical pathways and there are SOP clinical pathways, patient safety is guaranteed, comfort of patients in hospitals is very comfortable, treatment officers in the hospital for patients are also comfortable, information provided by officers to patients and families is quite clear, officers in providing services are always on time and responsive to patients, service is very helpful for patients and families in the era JKN. Concluded that the level of satisfaction by participants national health insurance hospital petala earth provinzi riau considered as a whole patient had been satisfied but need to be repaired. hospital services.